2014
DOI: 10.1002/2013jd020792
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological evaluation of the Noah‐MP land surface model for the Mississippi River Basin

Abstract: This study evaluates regional‐scale hydrological simulations of the newly developed community Noah land surface model (LSM) with multiparameterization options (Noah‐MP). The model is configured for the Mississippi River Basin and driven by the North American Land Data Assimilation System Phase 2 atmospheric forcing at 1/8° resolution. The simulations are compared with various observational data sets, including the U.S. Geological Survey streamflow and groundwater data, the AmeriFlux tower micrometeorological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
157
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 85 publications
3
157
0
1
Order By: Relevance
“…To initialize LSMs properly, the spin-up time required for LSMs to reach the equilibrium stage needs to be examined first (Chen and Mitchell, 1999;Cosgrove et al, 2003). In this study, model runs for the year 1998 were performed repeatedly until all the soil-state variables reached the equilibrium state, defined as when the difference between two consecutive 1-year simulations becomes less than 0.1 % for the annual means (Cai et al, 2014; L a te n t h e a t fl u x S e n s ib le h e a t fl u Yang et al, 1995). Yang et al (1995) discussed the spin-up processes by comparing results from 22 LSMs for grass and forest sites, and showed a wide range of spin-up timescales (from 1 to 20 years), depending on the model, state variable, and vegetation type.…”
Section: Noah-mp Model Spin-upmentioning
confidence: 99%
See 2 more Smart Citations
“…To initialize LSMs properly, the spin-up time required for LSMs to reach the equilibrium stage needs to be examined first (Chen and Mitchell, 1999;Cosgrove et al, 2003). In this study, model runs for the year 1998 were performed repeatedly until all the soil-state variables reached the equilibrium state, defined as when the difference between two consecutive 1-year simulations becomes less than 0.1 % for the annual means (Cai et al, 2014; L a te n t h e a t fl u x S e n s ib le h e a t fl u Yang et al, 1995). Yang et al (1995) discussed the spin-up processes by comparing results from 22 LSMs for grass and forest sites, and showed a wide range of spin-up timescales (from 1 to 20 years), depending on the model, state variable, and vegetation type.…”
Section: Noah-mp Model Spin-upmentioning
confidence: 99%
“…When using the groundwater component of Noah-MP, it might take at least 250 years to spin up the water table depth in arid regions (Niu et al, 2007). Cai et al (2014) found that water table depth requires less than 10 years to spin up in a wet region, but more than 72 years for a dry region. For this boreal forest site where the water table depth is shallower (less than 2.5 m), it takes ∼ 7 years for water table depth to reach equilibrium.…”
Section: Noah-mp Model Spin-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Model runs for 2001 were repeatedly performed for all scheme combinations until the variables reached equilibrium. The criterion for the equilibrium is defined as the time when the difference in annual means between two consecutive one-year simulations is less than 0.1 % of the means (Cai et al, 2014;Yang et al, 1995). The spin-up periods of the all scheme combinations were no more than two years, and their differences were quite small among the scheme choices even though the scheme choices in RUN showed the greatest differences.…”
Section: Model Sensitivity To Scheme Choices In a Physical Categorymentioning
confidence: 99%
“…Additionally, Noah-MP has different parameterizations for several key land surface processes (Table 2); therefore, it can be used to conduct ensemble model simulations. Various studies have confirmed the performance of Noah-MP in reproducing energy and water fluxes at various scales and under different hydrometeorological conditions [41][42][43].…”
Section: Noah-mp Lsmmentioning
confidence: 88%